2017
DOI: 10.1002/ejp.1031
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of Incobotulinumtoxin A on pain, neurogenic flare and hyperalgesia in human surrogate models of neurogenic pain

Abstract: The study demonstrates that BoNT/A (Incobotulinumtoxin A) has differential effects in human pain models: It reduces the neurogenic flare and had a moderate analgesic effects in low frequency but not high frequency current stimulation of cutaneous afferent fibers at C-fiber strength; BoNT/A had no effect in capsaicin-induced (CAPS) neurogenic flare or pain, or on hyperalgesia to mechanical or heat stimuli in both pain models. Intracutaneous BoNT/A increases warm and heat pain thresholds on naïve skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Non‐replicated studies reported positive results with hydrocortisone (Michaux et al., 2012 ), intrathecal adenosine (Eisenach et al., 2002 ), and epidural or intrathecal clonidine (Eisenach et al., , 1998 , 2000 ). Inconsistent results were observed with botulinum toxin (Diener et al., 2017 ; Gazerani et al., 2006 ). The tricyclic antidepressants amitriptyline and desipramine failed to modify 2HA in two studies (Eisenach et al., 1997 ; Wallace et al., 2002 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Non‐replicated studies reported positive results with hydrocortisone (Michaux et al., 2012 ), intrathecal adenosine (Eisenach et al., 2002 ), and epidural or intrathecal clonidine (Eisenach et al., , 1998 , 2000 ). Inconsistent results were observed with botulinum toxin (Diener et al., 2017 ; Gazerani et al., 2006 ). The tricyclic antidepressants amitriptyline and desipramine failed to modify 2HA in two studies (Eisenach et al., 1997 ; Wallace et al., 2002 ).…”
Section: Resultsmentioning
confidence: 90%
“…toxin (Diener et al, 2017;Gazerani et al, 2006). The tricyclic antidepressants amitriptyline and desipramine failed to modify 2HA in two studies (Eisenach et al, 1997;.…”
Section: Ha Areamentioning
confidence: 95%